Advancing Stability in Robot Manipulators: A Review of Recent Progress and Parameters - Shabnom Mustary; Mohammod Abul Kashem; Jannatul Mawya Sony; Nayem Hossain; Mohammad Asaduzzaman Chowdhury (Engineering Reports)
ABSTRACT In this review, we present an overview of the current state‐of‐the‐art in robotics while emphasizing stability and control aspects with pragmatic consideration over robotic manipulators. It is centered on robustness, efficiency, and security for applications such as industrial automation or surgical robotics. Advancements comprise advanced control algorithms, sensor technology, and new mechanical schemas (rigid, flexible and hybrid). Uses of Lyapunov and Passivity‐Based Control for key stability improvements incorporate robust solutions to nonlinear dynamics and uncertainties. Issues around calibration and optimizing manipulator performance (material properties, mass distribution, and friction effects) still exist. We will head toward compliant materials and anthropomorphic dexterity of future notions, which afford human‐like impedance as well as advanced sensory actuation devices providing model‐based perception coupled with cognitive deduction efforts to truly fulfill a much‐desired dream: the intuitive cooperation between humans and robots.